The Interrelations of Finance and Economics: Empirical Perspectives - Gibbons, Michael R. (American Economic Review, 2016)
The title of this paper is somewhat inappropriate, for it may suggest that finance is a study separate from economics. In fact, most researchers in finance refer to themselves as financial economists, and many have done their graduate work in departments of economics. A more appropriate (but longer) title would refer to the interrelations of financial economics and other fields in economics. Given finance is a field within economics, it is not surprising that finance has borrowed heavily from other disciplines within economics and that the reverse has occurred as well-although the latter is a newer phenomenon than the former. Financial economics has a long tradition of empirical work which will be the focus of this paper. I categorize the cross fertilization between finance and economics in the next four sections. The first section discusses the sharing of econometric methods. Section II focuses on situations where other fields in economics also attempt to explain prices of financial securities. Because of the quality and quantity of financial data, finance has served as an empirical laboratory for other fields in economics; this is discussed in the third section. Finally, since security prices are governed in part by expectations about future economic variables, there have been attempts to extract these expectations (as well as other unobservables) from the observed prices of financial assets. Section IV notes some examples of where unobservables have been extracted from prices of securities. Using financial data to measure the economic impact of certain events or to extract unobservables presumes that the participants in the financial market are rational. To the extent that this rationality assumption is violated calls into question the usefulness of financial data. Section V discusses some of the recent empirical anomalies in financial economics as well as their ramifications for employing financial data. This paper is not an exhaustive survey of all the interrelations between finance and economics. Instead the paper only attempts to illustrate some of the interrelations by relying on a few examples.